Menelisik Mitologi Masyarakat Kerinci dalam Naskah Incung Ini Asan Pulung - Hadi Sunliensyar, Hafiful (Jumantara: Jurnal Manuskrip Nusantara, 2024)
Ini Asan Pulung is one of the Incung manuscripts on bamboo found in Dusun Sungai Tutung, Kerinci. Based on previous research, the manuscript contains cosmological text related to cosmogony and the creation of human. However, the transliteration of the manuscript is incomplete. Therefore, the mythological elements in the manuscript are unknown clearly. The purpose of this research is to publicize the transliteration of Ini Asan Pulung manuscript completely and to explain the elements of mythology in the text. The research method used is descriptive research method with philological approach. This research is conducted in several stages. The first stage is data collection which works with an inventory of manuscripts and a literature review. The second stage is data processing encompasses describing, transliterating, and translating of the manuscript. The third stage is data analysis encompasses commentary and explanation of mythological elements. Transliteration of this manuscript uses the standard edition method to simplify the understanding of the public. The results of this study explain that the Ini Asan Pulung manuscript contains cosmogony myth, creation of human myth (anthropogenic myth), the creation of supernatural beings myth, the relation of human and supernatural beings entities myth, and the cosmology of Kerinci society.